Da pessoa que recai a pessoa que se levanta: a recursividade dos que usam crack - Rameh-de-Albuquerque, Rossana Carla [UNIFESP] (2017)
Although available treatments for crack abuse reduce the gravity of the psychosocial problems caused by usage, they have not been able to solve drug abuse “relapses” until now. Hoping to increase the knowledge around the theme, this qualitative research thesis aims to investigate reasons for relapse among abusive crack users –who, in their final treatment phase have relapsed. To develop the study, the search field included three venues: the Centers of Psychosocial Attention in alcohol and other drugs (Caps AD), the Therapeutic Communities (CT) and Medical Clinics (CM). Principles of qualitative investigation were used along with samples chosen for set criteria, built with the help of the key-informants (gatekeepers), and semi-structured interviews which were applied to the research participants. Reaching a theoretical saturation point, 120 people were equally divided between the greater metropolis regions of Recife – PE and São Paulo – SP. Analysis of the content revealed categories that emerged from the interviewees’ narratives. Didactically narratives were divided into three thematic blocks: reasons associated with people (MP), reasons associated twith the drug (MD), reasons associated with the environment (MA). Within these blocks, those most reported were the ones related to the MP category, which were highly relevant to the difficulty and/or inability people have to deal with their emotions. Aspects which defined the concept of “relapse” as inappropriate also revealed the phenomenon of reading through the light of Harm Reduction based on Human Rights, considering the principle of recursivity as a fundamental starting point to another perception over the phenomenon. Some final considerations were reached: people’s interpersonal relations and the consequent frustrations were the mostly cited reasons for unleashing “relapse”, breaking the paradigm that says the causes are centered mainly on the drug itself.In addition, the intersubjective processes which refer to people’s recursive movements showed that their knowledge and resignifications over crack are neglected aspects of treatment, by professionals and caretakers, independent of the model by which care instances are affiliated. It is expected that these findings can contribute to an improvement of the attention given to crack users who search for treatment.